2020
DOI: 10.1167/tvst.9.8.29
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Changes in Tear Lipid Layer Thickness After Instillation of Lipid Containing Eye Drops

Abstract: Lipid-containing eye drops is increasingly popular in eye clinics to treat dry eye. Tear lipid layer thickness (LLT) changes after instillation of lipid eye drops have not been characterized. We aim to evaluate these changes of LLT using a noninvasive interferometry-based method. Methods: This prospective clinical study was conducted on staff and patients from Singapore National Eye Centre with ad hoc recruitment. Noninvasive tear break up time was measured using the Keratographer 5M. LLTs were measured using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Phospholipids are commonly used in the manufacture of liposomes [9] to increase the thickness of the lipid layer. Our results are consistent with studies that show an increase in LLT after the instillation of drops that include lipids in their composition [32,[34][35][36]. However, in the HA group, the thickness of the lipid layer decreased at 30 min (0.50 ± 0.51 degrees on the Guillon Scale) (p = 0.01) and 45 min (0.04 ± 0.55 degrees on the Guillon Scale) (p = 0.70).…”
Section: Lipid Layer Thicknesssupporting
confidence: 91%
“…Phospholipids are commonly used in the manufacture of liposomes [9] to increase the thickness of the lipid layer. Our results are consistent with studies that show an increase in LLT after the instillation of drops that include lipids in their composition [32,[34][35][36]. However, in the HA group, the thickness of the lipid layer decreased at 30 min (0.50 ± 0.51 degrees on the Guillon Scale) (p = 0.01) and 45 min (0.04 ± 0.55 degrees on the Guillon Scale) (p = 0.70).…”
Section: Lipid Layer Thicknesssupporting
confidence: 91%
“…The women included in the study were taking oral contraceptives that negatively influence lipid production, generating dry eye by evaporation. Currently, it is very common to include lipids in the composition of artificial tears since their efficacy was shown to improve LLT and reduce tear film evaporation [ 34 , 35 , 36 , 37 ]. In our study, no eye drops contained lipids in their composition, and this situation might explain why there were no changes in LLT or an increase in TMH.…”
Section: Discussionmentioning
confidence: 99%
“…The LLT, blink rates, partial blink ratios and CVS-Q score were further analyzed between participants with high (≥60) and low (<60) baseline LLTs. The cutoff value was 60 nm because previous studies reported that a thin LLT (<60 nm) significantly correlated with DED ( 23 , 29 ). Korb et al investigated how blinking improved LLT and found that subjects with baseline LLT values < or = 60 nm experienced a mean increase of 19 nm of LLT after forceful blinking ( 30 ).…”
Section: Methodsmentioning
confidence: 99%